Serbia: An Ongoing Harmonisation of State Aid Rules - Popović, Dušan V. (Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries, 2024)
European state aid control extends its influence beyond the borders of the European Union. Traces of the methods and approaches enshrined in Arts. 107 and 108 of the Treaty on the Functioning of the European Union can be found both in the domestic legal order of non-EU jurisdictions and in the trade agreements concluded between EU and non-EU countries, like the Republic of Serbia. The legislative framework for state aid control in Serbia is broadly in line with the EU acquis and the relevant provisions of the Stabilisation and Association Agreement concluded between EU and Serbia. Considering how European integration of Serbia is an ongoing process leaves limited space for an autonomous state aid policy in areas that are not yet fully aligned with EU law. Fiscal aid schemes have been identified as a domain in which Serbian state aid law differed from its EU counterpart for a significant period of time. Moreover, Serbia is yet to adopt its regional aid map. The drafting of the map is entrusted to the ministry in charge of regional development, and the draft map is to be assessed by both the Commission for State Aid Control and the European Commission. Until a regional aid map is drawn up, the entire national territory is considered an area with a GDP per capita of less than or equal to 45% of the EU-27 average. Keywords: state aid, Serbia, competition policy, European integration, regional aid